PENGARUH VARIASI BOARD DAN KEPEMILIKAN TERHADAP DIVIDEND PAYOUT PADA PERUSAHAAN SEKTOR PERTANIAN YANG TERDAFTAR DI BURSA EFEK INDONESIA - Yanita Marfiyanti; Justina Ade; Rizky Yudaruddin (Jurnal Ilmu Manajemen Mulawarman (JIMM), 2018)
This study aims to determine the effect of the number of directors, female directors and institutional ownership of dividend payout. The data used are secondary data obtained from the financial statements of agricultural enterprises listed on the Indonesia Stock Exchange in 2011-2015. The sample used in this study is 14 companies by using purposive sampling technique. Analyzer used for this study is Descriptive Statistic Analysis, Panel Data Regression, Classical Assumption Test and Hypothesis Test. The results of this study indicate that the results of hypothesis testing shows the number of directors have a significant positive effect on dividend payout. Female directors show an insignificant negative to dividend payout. And significant negative institutional ownership of dividend payout